Costa Rica: Agricultural R&D indicators factsheet - Stads, Gert-Jan; de los Santos, Luis (International Food Policy Research Institute, 2022)
Costa Rica has the largest agricultural research system in Central America, both in terms of investment and human resource capacity. Costa Rica stands out from other Central American countries in that its higher education section plays a preponderant role in the country’s agricultural research system. Despite spending more than other Central American on agricultural R&D in absolute terms, Costa Rica’s investment levels relative to agricultural GDP rank second in the region behind Panama. In 2020, Costa Rica spent 0.87 percent of its agricultural GDP on agricultural R&D, which was lower than ratios recorded a decade earlier. Costa Rica’s agricultural research capacity has gradually increased over the past decade. The rise in researcher numbers was largely driven by INTA, which recruited a considerable number of young, BSc-qualified researchers after a prolonged period of civil servant recruitment restrictions and the loss of senior scientists to retirement. INTA still lacks a critical mass of PhD-qualified researchers compared to the higher education sector.